Influence of Participation, Information and Learning Process on Agribusiness Competence of Pepper Farmers - Komariyati Komariyati; Endang Siti Rahayu; Mulyanto Mulyanto; Joko Sutrisno (AIBPM Publisher, 2022)
This study aims to analyze the effect of participation in community institutions, access to information sources and the learning process on the agribusiness competence of pepper farmers . The research method uses quantitative. The population is farmers in 14 (fourteen) sub-districts of the West Kalimantan Border Region. The sampling technique used was multistage cluster sampling . The number of samples was 160 pepper farmers. Data collection techniques using questionnaires and documentation. The data processing and analysis technique used Structural Equation Modeling (SEM). The results of the study concluded that: (1) participation in community institutions had a significant effect on the pepper farmer 's learning process; ( 2) access to information sources has a significant effect on the farmer's learning process ; (3) the farmer's learning process has a significant effect on the agribusiness competence of pepper farmers; (3) the farmer learning process becomes a mediating variable for the influence of participation in community institutions and access to information sources on the agribusiness competence of pepper farmers on the border of West Kalimantan, Indonesia.Keywords: Participation, Information, Learning Process, Agribusiness Competence